Programming with GitHub Copilot Write Better Code--Faster! - Dowswell, Kurt (John Wiley & Sons, Incorporated, 2024)
Accelerate your programming with the most popular AI coding tool on the market: GitHub Copilot In Programming with GitHub Copilot: Write Better Code -- Faster, veteran software developer and GitHub community hero Kurt Dowswell delivers an insightful and hands-on exploration of GitHub's powerful, new AI coding assistant, Copilot. In the book, you'll discover how to use the tool's capabilities to push the boundaries of what you thought was possible in programming. Even if you've used autocomplete tools--like VS Code's TabNine extension--before, you'll be floored by GitHub Copilot's potential to transform the way you code. You'll learn how to install, configure, and use the software, from employing it's most common and widely used features to deploying business and enterprise functionality. You'll even discover how to fix runtime and compilation bugs and write unit, integration, and end-to-end tests. You'll also find: Prompt strategies to get GitHub Copilot to help you brainstorm new code solutions What the future looks like for AI-assisted coding, including discussions of issues like code licensing and ethics Directions for chatting with Copilot, including common commands and prompts to help you guide the conversation to where you want it to go Perfect for practicing programmers, developers, and software engineers, Programming with GitHub Copilot is also an essential resource for coders and other IT practitioners-in-training who want to expand their knowledge and improve the scope and depth of their programming skillsets.
Description based upon print version of record. - Creating a Console Application
Keywords: Git (Computer file); Computer software -- Development